The Point of the Step-Parallelism in Luke 1–2 - Kuhn, Karl A. (New Testament studies, 2001)
It has long been noted by interpreters that Luke's birth narrative offers a comparative portrayal of Jesus and John, with the effect that Jesus is seen as the greater of the two (a feature of the text commonly called ‘step-parallelism’). Several explanations for this narrative device have been offered by commentators, including the proposal that the step-parallelism serves as an apologetic response to a messianic sect proclaiming John the Baptist as the Christ. This paper argues that while apologetic concerns may play a role, the primary motivation for the contrast Luke composes between the two characters is christological. In short, the point of the step-parallelism is to show that in preparing the way for God, John is really preparing the way for Jesus, because Jesus represents Yahweh in his mission and person.